Survival of Batrachochytrium dendrobatidis in Water: Quarantine and Disease Control Implications - Megan L. Johnson; Richard Speare (Emerging Infectious Diseases, 2003)
Amphibian chytridiomycosis is an emerging infectious disease of amphibians thought to be moved between countries by trade in infected amphibians. The causative fungus, Batrachochytrium dendrobatidis, produces aquatic, motile zoospores; infections have been achieved in experiments by exposing amphibians to water containing zoospores. However, the ability of this fungus to survive in the environment in the absence of an amphibian host is unknown. We show that B. dendrobatidis will survive in tap water and in deionized water for 3 and 4 weeks, respectively. In lake water, infectivity was observed for 7 weeks after introduction. The knowledge that water can remain infective for up to 7 weeks is important for the formulation of disease control and quarantine strategies for the management of water that has been in contact with amphibians.